Structural Policies for Shock-Prone Developing Countries. - Collier, P; Goderis, B (CSAE (University of Oxford), 2009)
Many developing countries periodically face large adverse shocks to their economies. We study two distinct types of such shocks - large declines in the price of a country’s commodity exports and severe natural disasters - , both of which have occurred frequently in the recent past. Unsurprisingly, adverse shocks reduce the short-term growth of constant-price GDP and we analyze which structural policies help to minimize these losses. Structural policies are incentives and regulations that are maintained for long periods, contrasting with policy responses to shocks, the analysis of which has dominated the literature. We show that some previously neglected structural policies have large effects that are specific to particular types of shock. In particular, regulations which reduce the speed of firm exit substantially increase the short-term growth loss from adverse non-agricultural export price shocks and so are particularly ill-suited to mineral exporting economies. Natural disasters appear to be better accommodated by labour market policies, perhaps because such shocks directly dislocate the population.